Single-lung ventilation technique in neonates undergoing thoracoscopic repair of esophageal atresia: a single-center retrospective cohort study - Zhang, Fan; Zhou, Zhijian; Liu, Yingbei; Wang, Xuan (Frontiers in Surgery, 2024)
BackgroundThoracoscopic repair is a common surgical procedure to treat esophageal atresia (EA). During thoracoscopic surgery, the single-lung ventilation (SLV) technique is used to collapse one of the lungs to obtain a better surgical view. However, SLV is associated with risks in neonates. This study aimed to assess the perioperative benefits and risks of SLV in neonates who underwent thoracoscopic EA repair.MethodsThis single-center retrospective cohort study included all neonates who underwent thoracoscopic repair of EA at the Children's Hospital of Fudan University between January 1, 2016 and December 31, 2021. Neonates were assigned to SLV (Group S) or dual-lung ventilation (DLV, Group D) groups depending on the technique used intraoperatively. The intraoperative and postoperative information of the two groups were compared.ResultsA total of 70 neonates were included in this study. Twenty-nine neonates were assigned to Group S and forty-one to Group D. No intraoperative adverse events were observed in either group. The surgery time of Group S was significantly shorter than that of Group D (81 ± 23 and 99 ± 29 min, respectively, P = 0.004). In contrast, the anesthetic preparation time of Group S was significantly longer than that of Group D (54 ± 22 and 44 ± 16 min, respectively, P = 0.030). The frequency of postoperative adverse events in Group S was similar to that of Group D (31.03% and 40.54%, respectively, P = 0.453).ConclusionSLV was associated with a reduced surgery time for thoracoscopic repair of EA and longer anesthetic preparation time compared to DLV. The SLV was as safe as the DLV with potential advantages in thoracoscopic EA repair.